Benefits and costs of immune memory in Rhodnius prolixus against Trypanosoma cruzi. (April 2022) - Carmona-Peña, S.P.; Vázquez-Chagoyán, J.C.; Castro, D.P.; Genta, F.A.; Contreras-Garduño, J.
Abstract: There is increasing evidence supporting the immune memory in invertebrates, but the studies are relatively neglected in insect vectors other than mosquitoes. Therefore, we tested two hypotheses: 1) Rhodnius prolixus insects possess immune memory against Trypanosoma cruzi, and 2) their immune memory is costly. The Dm28c and Y strains of T. cruzi were used, the former being more infective than the latter. On the one hand, the triatomines subjected to dual challenges with the Dm28c strain did not show significant differences in survival than those of the heterologous challenge groups control-Dm28c and Y-Dm28c. On the other hand, the insects survived longer after a dual Y–Y challenge than after the corresponding heterologous challenge (control-Y). The Y–Y, Dm28c-Y, and naïve groups showed similar survival. There was more prolonged survival following the Y–Y versus Dm28c-Dm28c dual challenge. The Dm28c-Dm28c group exhibited moulting sooner than the control-Dm28c or naïve group. In contrast, there were no differences in the probability of moulting between the Y–Y and naïve groups. The results suggest that triatomines have immune memory against the Y but not the Dm28c strain. Further investigation on triatomine and T. cruzi interaction is needed to determine if infectivity accelerates or delay growth due to innate immune memory. Highlights: We investigated if Rhodnius prolixus have innate immune memory against two strains of Trypanosoma cruzi. We compared survival and development between the Naïve (only manipulated), Control and Memory groups. We found innate immune memory against the Y strain but not against the Dm28c strain. We showed differential cost of innate immune memory according to the parasite strain. Our results ask whether the costs of innate immunity or a growth acceleration strategy favor developmental plasticity.